2002
DOI: 10.1300/j017v19v04_02
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Modern Technology and Internet Access for Under-Represented Older Populations

Abstract: Bridging the Gap, a South Australian research based program, was designed to introduce the concepts of modern technology and some Internet skills to people over 55. Target populations included people in rural areas, those with a first language other than English and people who were frail or had a disability. Informal, interactive, hands-on Carol Irizarry, PhD, a Canadian, is Senior Lecturer at ). She has conducted research with state and federal funding into how technology can contribute to older people's qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…Computers and the Internet have the potential to improve older peoples' quality of life by providing them access to interesting relevant and useful information as well as the opportunity to interact with other people. Generally, older people are willing to use computers but they often experience difficulties in adopting new technology [6,15]. It has been shown that resistance to computers can be overcome by direct experience but also by familiarity engendered by having computers in their environment used by others [6,15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Computers and the Internet have the potential to improve older peoples' quality of life by providing them access to interesting relevant and useful information as well as the opportunity to interact with other people. Generally, older people are willing to use computers but they often experience difficulties in adopting new technology [6,15]. It has been shown that resistance to computers can be overcome by direct experience but also by familiarity engendered by having computers in their environment used by others [6,15].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, older people are willing to use computers but they often experience difficulties in adopting new technology [6,15]. It has been shown that resistance to computers can be overcome by direct experience but also by familiarity engendered by having computers in their environment used by others [6,15]. Older adults may want to feel part of the modern world and welcome the opportunity that technology may offer to facilitate social contact with their family (e.g., children and grandchildren) who have made computers and the Internet an inherent part of their lives [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors, viewed collectively, reflect how theorists have evolved notions of digital exclusion from initial conceptualisations based principally on access. The factors comprising the technological divide framework were identified as a result of three separate empirical studies featuring a total of 2345 participants (Irizarry, Downing & West, 2002;Irizarry, West & Downing, 2001;West, 2003a;West, 2003b). Understanding that access, knowledge and awareness, learning opportunities and support, and skills all contribute to the successful use of technology performs the dual function of helping researchers to pinpoint appropriate research questions and assisting practitioners at all levels to target social interventions at specific The right hand column entitled "outcomes & process" represents the practical application of the framework in the context of the broader goal to globally improve the social justice outcomes associated with digital exclusion.…”
Section: T H E S O C I a L W O R K P E R S P E C T I V Ementioning
confidence: 99%